HOW PYTHON AND SQL ARE USED IN BIG DATA ANALYTICS AND HOW THEY ENABLE REAL TIME ANALYTICS OF DATA - Amber Chowdhary (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This article explores the transformative role of Python and SQL in big data analytics and their combined capabilities in enabling real-time data processing. The article examines how Python's distributed computing frameworks and SQL's query optimization techniques have revolutionized healthcare analytics, scientific computing, and enterprise data processing. Through comprehensive analysis of various implementation scenarios, the article demonstrates the significant improvements achieved in data processing efficiency, resource utilization, and analytical accuracy when both technologies are integrated. The article also investigates key technologies in real-time analytics, including stream processing platforms, open-source engines, cloud-native services, and distributed database systems, highlighting their impact on modern data-driven decision-making processes.